Depth and Breadth of Mathematics Syllabus for engineering technology students in UniversitiTun Hussein Onn Malaysia - Jalani, Jamaludin; Norjali, Rasida; Mashori1, Sumaiya; Sadun, AmirulSyafiq; Ali, Roslinda (2020)
The Faculty of Engineering Technology (FTK), University Tun Hussein Malaysia (UTHM) is currently developing the Engineering Technology program. Note that there are differences between classical engineering as compared toengineering technology program. In particular, the curriculum of both program has to be different. According to Accreditation Board for Engineering and Technology (ABET),Engineering programs often focus on theory and conceptual design, while engineering technology programs usually focus on application and implementation. In addition, Engineering programs require additional, higher-level mathematics, including multiple semesters of calculus and calculus-based theoretical science courses. Meanwhile, engineering technology programs typically focus on algebra, trigonometry, applied calculus, and other courses that are more practical than theoretical in nature.Here, the study is carried out to investigate the depth and breadth of mathematics syllabus taught by the FTK in UTHM.An online survey has been conducted. The respondents are engineers who are currently working all over Malaysia. The respondents are required to scale from the most significant to the least significant of 18 different topics of mathematics that related to their working environment. The results show that the majority of respondents agree to maintain the chapters taught in the classproposed by the FTK. However, some topics are not related to the industries can be eliminated from the syllabus.